Like in Old Glorious Times - Östergård, Johannes (Germany : HFF Münich, 2009)
"Like in Old Glorious Times" is a musical documentary following Russian born multi instrumentalist Andre Solomko as he fights the digital world with his "Vinyl Jam" project: analog tapes, tube amplifiers and shiny black vinyl records. Like scientists he and his companion Vladimir are trying to find the perfect analog jazz-rock sound in their little studio in the middle of the Finnish forest. Recording together with a band of young musicians they embark on a quest for perfection.
Verzio Film Festival Submission
Verzio Film Festival Submission
Keywords: Documentary films